2021
DOI: 10.1136/bmj.n160
|View full text |Cite
|
Sign up to set email alerts
|

PRISMA 2020 explanation and elaboration: updated guidance and exemplars for reporting systematic reviews

Abstract: The PRISMA 2020 statement includes a checklist of 27 items to guide reporting of systematic reviews In this article we explain why reporting of each item is recommended, present bullet points that detail the reporting recommendations, and present examples from published reviews We hope that uptake of the PRISMA 2020 statement will lead to more transparent, complete, and accurate reporting of systematic reviews, thus facilitating evidence based decision making on 15 April 2021 by guest. Protected by copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
3,449
1
140

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 5,366 publications
(3,599 citation statements)
references
References 205 publications
9
3,449
1
140
Order By: Relevance
“…We have prepared an updated explanation and elaboration paper, in which we explain why reporting of each item is recommended and present bullet points that detail the reporting recommendations (which we refer to as elements) 41. The bullet-point structure is new to PRISMA 2020 and has been adopted to facilitate implementation of the guidance 6061.…”
Section: The Prisma 2020 Statementmentioning
confidence: 99%
“…We have prepared an updated explanation and elaboration paper, in which we explain why reporting of each item is recommended and present bullet points that detail the reporting recommendations (which we refer to as elements) 41. The bullet-point structure is new to PRISMA 2020 and has been adopted to facilitate implementation of the guidance 6061.…”
Section: The Prisma 2020 Statementmentioning
confidence: 99%
“…However, for updated and living systematic reviews, there may be some additional considerations that need to be addressed. Where there is relevant content from other reporting guidelines, we reference these guidelines within the items in the explanation and elaboration paper [41] (such as PRISMA-Search [42] in items 6 and 7, Synthesis without meta-analysis (SWiM) reporting guideline [27] in item 13d). Box 1 includes a glossary of terms used throughout the PRISMA 2020 statement.…”
Section: Scope Of the Guidelinementioning
confidence: 99%
“…We have prepared an updated explanation and elaboration paper, in which we explain why reporting of each item is recommended and present bullet points that detail the reporting recommendations (which we refer to as elements). [41] The bullet-point structure is new to PRISMA 2020 and has been adopted to facilitate implementation of the guidance. [60,61] An expanded checklist, which comprises an abridged version of the elements presented in the explanation and elaboration paper, with references and some examples removed, is available in S2 PRISMA 2020 expanded checklist.…”
Section: How To Use Prisma 2020mentioning
confidence: 99%
“…All non-health science manuscripts that assess authorship issues will also be presented in the list of excluded studies with the reason for exclusion. The study selection procedures will be reported in a PRISMA ow chart [36,37].…”
Section: Data Management and Selection Processmentioning
confidence: 99%